Dynamic Modeling and Simulation of Mechanical System Based on Dynamic Test Data - Chen, Huabing (Proceedings of the The 1st EAI International Conference on Multimedia Technology and Enhanced Learning, 2016)
In this paper, a dynamic model of mechanical system based on experimental data is proposed by combining the physical simulation and computer simulation. System level model updating is a key issue in modern mechanical design, such as flexible multibody system dynamics modeling, mechanism dynamics modeling and joint modeling and so on. In this paper, the dynamic simulation of mechanical system based on dynamic experimental data is carried out, which is based on the two aspects of the vibration problem and the dynamic balance of mechanism. For the mechanical system based on vibration, the simulation results are close to the experimental results by modifying the modal damping ratio of the components and the parameters of the flexible joint. For institutions comprehensive dynamic balance problem by means of computer simulation, and designed an optimization process for this kind of problems. It also uses the contrast experiment to modify the structural modal damping ratio, respectively, to verify the effectiveness of optimization and the method of correction. The mechanical system dynamics analysis, the first step is to build up the basic model of flexible multibody systems, in order to obtain better results, but also need to further realize the mechanical system dynamics pre correction model then by digital simulation to guide the design finally from the experimental data according to the starting, through comparison of experiment and simulation, the important parameters of the system level model modified, so as to establish the digital simulation model based on experimental data. By comparison with the experiment shows that, the method in this paper can not only trend prediction effect, also can obtain more accurate simulation results, from the experimental and simulation combined with this point of view to explore the mechanical system dynamics simulation analysis method.